2021
DOI: 10.3390/atoms9030063
|View full text |Cite
|
Sign up to set email alerts
|

Emission Lines in 290–360 nm of Highly Charged Tungsten Ions W20+–W29+

Abstract: Forbidden transitions in the near-UV and visible wavelength of highly charged tungsten (W) ions are potentially useful as novel tungsten diagnostics means of fusion plasmas. Emission lines in 290–360 nm from Wq+ ions interacting with an electron beam of 540–1370 eV are measured, using a compact electron-beam-ion-trap. The charge states of 64 lines are identified as W20+–W29+. A magnetic-dipole (M1) line of W29+ between the excited states (4d84f)[(4d5/2−2)44f7/2]13/2→[(4d5/2−2)44f5/2]13/2 is newly identified; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Our study complements recent works from other groups that have investigated various interesting ionic species, for instance [22][23][24][25][26][27][28][29][30], using electron beam ion traps (EBITs). These works also emphasized heavy ions, orbital crossings, and hyperfine structure studies (e.g.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…Our study complements recent works from other groups that have investigated various interesting ionic species, for instance [22][23][24][25][26][27][28][29][30], using electron beam ion traps (EBITs). These works also emphasized heavy ions, orbital crossings, and hyperfine structure studies (e.g.…”
Section: Introductionsupporting
confidence: 74%
“…Lifetime measurements of optical transitions in Mo XXII were reported in [33]. Some more of those investigations are listed here: [34] reported W VI to W VIII spectra; [30] analyzed the spectra of Pm-like W XIV; [23] worked on W VIII; [26] re-assessed earlier work on W XII; [35] analyzed W XIII; W XIV was studied in [36]; in [27] observed spectra from ions W XXI up to W XXX were reported. Spectral data from Yb and W were recorded in [25], where the In-like Yb XXII and W XXVI and Sn-like W XXV were compared with detailed calculations.…”
Section: Introductionmentioning
confidence: 99%
“…However, further studies, especially in multivalent CR modeling, should be conducted to determine the valence state attribution of this spectral line. In the wavelength range of 290-475 nm, a total of 30 lines [21,22] have been reported. The dense distribution of spectral lines poses a considerable challenge in terms of line identification.…”
Section: Nomentioning
confidence: 99%
“…Over the decade, some efforts have been made in both theoretical calculations and experiments. Komatsu et al [21] and Era et al [22] provided a total of 30 spectral lines in the wavelength range of 290-475 nm using CoBIT-II and CoBIT, respectively. Murata et al [18] observed six more lines in the 580-850 nm range and identified two using the CI + all-order method.…”
Section: Introductionmentioning
confidence: 99%